Production method of high-crack-arrest extra-thick high-strength ship plate

Through the DQ+LT process, the phase change structure of the extra-thick and high-strength ship plate is regulated to form a multi-phase structure, which solves the problem of insufficient crack-resistance performance of the extra-thick ship plate in the prior art, and realizes the production of extra-thick ship plates with high crack-resistance and high-strength super-thick ship plates.

CN119571215APending Publication Date: 2025-03-07HUNAN VALIN XIANGTAN IRON & STEEL CO LTD

Patent Information

Application Number
CN202411743684.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-30
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively improve the crack-resistance performance of ultra-thick high-strength ship plates for container ships, especially in terms of improving the tough structure at the 1/2 position of the plate thickness.

Method used

The DQ+LT process is adopted to accurately control the phase change structure after rolling through a two-step heat treatment process, forming a small multiphase structure, eliminating tissue defects and refining grains, thereby improving the crack-resistance performance of the extra-thick steel plate.

Benefits of technology

The production of high-strength ship plates with high-strength crack-resistance is achieved, with a maximum thickness of 100mm, and the crack-resistance toughness Kca≥8000N/mm3/2 in -10℃, meeting the use needs of key parts of super-large container ships.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571215A_ABST
    Figure CN119571215A_ABST
Patent Text Reader

Abstract

The invention discloses a production method of a high-crack-arrest extra-thick high-strength ship plate, and belongs to the field of steel material preparation. The steel comprises the following chemical components in percentage by weight: 0.05%-0.08% of C, less than or equal to 0.50% of Si, 1.20%-1.60% of Mn, less than or equal to 0.010% of P, less than or equal to 0.002% of S, 0.015%-0.05% of Al, 0.01%-0.04% of Nb, 0.02%-0.05% of V, 0.008%-0.02% of Ti, 0.20%-0.50% of Ni, less than or equal to 0.20% of Cr, less than or equal to 0.20% of Cu and the balance of Fe and inevitable impurities. The method breaks through the limitation of the compression ratio of the ultra-thick crack-arrest steel rolled by the continuous casting billet, adopts the online DQ + LT process to regulate and control the soft and hard phase structures, produces the ultra-thick crack-arrest steel plate with the maximum thickness of 100mm by using the continuous casting billet, integrates high strength, high toughness and high crack-arrest performance, and is simple in process, low in production cost and suitable for large-scale production. And a solution is provided for producing the high-crack-arrest super-thick high-strength ship plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of steel material preparation and relates to a method for producing a high-crack-arresting, extra-thick and high-strength ship plate. Background Art

[0002] With the development of the world economy and the increase in trade volume, container ships are gradually developing in the direction of large-scale development. The load-bearing load of the upper structure of the deck of container ships is also increasing. Some key parts, such as the main deck, the side top plate, the hatch coaming, etc., require high strength, high toughness and high crack arrest performance, and the general high-strength ship plate can no longer meet the use requirements. Taking the 24000TEU ultra-large container ship as an example, the thickness of the hatch coaming reaches 95mm, and the amount of crack arrest steel alone is more than 1000 tons / ship. Japan began to develop crack arrest steel plates as early as the 1990s and used this steel plate in Japanese shipyards for the first time. In 2013, the International Ship Federation (IACS) and some classification societies drew on Japan's development experience and formulated a standard for crack arrest steel plates for container ships specifically for the key parts of large container ship plates, and listed ESSO tests and brittle fracture tests such as double tension as methods for testing the crack arrest performance of steel plates.

[0003] In order to improve the performance of crack arrest steel plates for container ships, some countries have conducted a lot of exploration. Chinese patent CN101341269 A "High-strength thick steel plate with excellent crack arrest performance" mainly controls the differences in the organization, grain boundary density and texture of the steel plate in the thickness direction, so that the crack propagation direction of the steel plate at different thickness positions when cracking is different, thereby increasing the crack propagation resistance to improve the crack arrest performance of the steel plate. However, the essence is that the cooling capacity of the thick plate produced by it is insufficient, and the brittle structure at the 1 / 2 position of the plate thickness affects the crack arrest performance of the steel plate. This method has little improvement in crack arrest performance and has not fundamentally improved the toughness structure at the 1 / 2 position.

[0004] Chinese patent CN 102994874 A "Yield strength 500Mpa grade high crack arrest toughness steel plate and its production method" discloses a method of refining grains and preventing crack propagation by rough rolling and then rapidly cooling to near the Ar3 phase transition point for fine rolling. However, this method uses low temperature impact toughness and NDT tough-brittle transition temperature to measure the crack arrest performance of the steel plate, which is not scientific and rigorous. It can only indicate that the toughness of the steel plate is good, but cannot prove that the crack arrest performance of the steel plate is excellent. Only the ESSO test or double tensile test is the internationally recognized standard test for measuring the crack arrest performance of steel plates. Summary of the invention

[0005] The purpose of the present invention is to provide a method for producing a high-crack arresting, extra-thick, high-strength ship plate, which relates to a method for producing a high-strength ship plate with a yield strength of 32, 36, or 40 kg, and a particularly -10°C crack arrest toughness Kca ≥ 8000 N / mm3 / 2 , with high crack arrest properties.

[0006] The technical solution of the present invention: A method for producing a high-crack-arresting, extra-thick, high-strength ship plate, the production process steps comprising: smelting, continuous casting, heating, rolling, cooling, quenching, and tempering. The chemical composition and weight percentage of the steel are: C=0.05%~0.08%, Si≤0.50%, Mn=1.20%~1.60%, P≤0.010%, S≤0.002%, Al=0.015%~0.05%, Nb=0.01%~0.04%, V=0.02%~0.05%, Ti=0.008%~0.02%, Ni=0.20%~0.50%, Cr≤0.20%, Cu≤0.20%, the remainder is Fe and unavoidable impurities; the key process steps include: heating furnace temperature 1180~1220℃; rolling adopts controlled rolling, and the final rolling temperature is 820~850℃; cooling adopts rapid water cooling to room temperature, and the cooling rate is ≥5℃ / s; quenching adopts two-phase zone quenching, and the quenching temperature is A c1 +(10~30)℃, quenching time is 3.0min / mm×plate thickness+(15~25)min; tempering adopts critical tempering, and the tempering temperature is A c1 -(20~60)℃, tempering time is 2.5~3.0min / mm×plate thickness min; among which, A c1 It is the starting temperature of the transformation of ferrite to austenite during the heating process.

[0007] A further solution is a method for producing a high-crack-arresting, extra-thick, high-strength ship plate with a yield strength of 32 kg, wherein the chemical composition of the steel and its weight percentage are: C=0.05%~0.07%, Si=0.15%~0.35%, Mn=1.30%~1.40%, P≤0.010%, S≤0.002%, Al=0.015%~0.050%, Nb=0.01%~0.02%, V=0.02%~0.03%, Ti=0.008%~0.02%, Ni=0.20%~0.30%, and the remainder is Fe and unavoidable impurity elements; accordingly, preferably, the quenching temperature is 720~740°C, and the tempering temperature is 665~695°C.

[0008] A further solution is a method for producing a high-crack-arresting, extra-thick, high-strength ship plate with a yield strength of 36 kg, wherein the chemical composition of the steel and its weight percentage are: C=0.05%~0.07%, Si=0.15%~0.35%, Mn=1.40%~1.50%, P≤0.010%, S≤0.002%, Al=0.015%~0.050%, Nb=0.02%~0.03%, V=0.03%~0.04%, Ti=0.008%~0.02%, Ni=0.30%~0.40%, Cr=0.10%~0.18%, and the remainder is Fe and unavoidable impurity elements; accordingly, preferably, the quenching temperature is 725~745°C, and the tempering temperature is 660~690°C.

[0009] A further solution is a method for producing a high-crack-arresting, extra-thick, high-strength ship plate with a yield strength of 40 kg, wherein the chemical composition of the steel and its weight percentage are: C=0.06%~0.08%, Si=0.15%~0.35%, Mn=1.50%~1.60%, P≤0.010%, S≤0.002%, Al=0.015%~0.050%, Nb=0.03%~0.04%, V=0.04%~0.05%, Ti=0.008%~0.02%, Ni=0.40%~0.50%, Cr=0.10%~0.18%, Cu=0.10%~0.18%, and the remainder is Fe and unavoidable impurity elements; accordingly, preferably, the quenching temperature is 730~750°C, and the tempering temperature is 660~690°C.

[0010] The process technology principle of the present invention: The present invention is different from the traditional crack arrest steel production process. It does not use the TMCP process to refine the grains to improve the crack arrest of the steel plate, but uses the DQ+LT process and a two-step heat treatment process to accurately control the phase transformation structure after rolling to form a fine multiphase structure, eliminate structural defects and refine the grains at the same time, so as to achieve the purpose of improving the crack arrest of the extra-thick steel plate. The rolled structure is mainly lath bainite + granular bainite + M / A island, especially in the core of the extra-thick steel plate, the size and proportion of granular bainite and M / A island increase, which seriously deteriorates the toughness and crack arrest; the first step is to quench the steel plate in the two-phase zone and heat it to A c1+(10~30)℃, the rolled structure undergoes partial reverse transformation to obtain reverse transformed austenite. The reversed austenite is dispersed along the original austenite grain boundaries and between the lath structures to achieve partial austenitization. The unaustenitized matrix structure still maintains the lath structure, and the elements such as C, Mn and Ni in the matrix structure are enriched in the reversed austenite, thereby improving the hardenability of the reversed austenite. In the subsequent water cooling process, the reversed austenite is transformed into martensite or bainite, while the unaustenitized structure with depleted C, Mn and Ni content is transformed into critical ferrite. Due to the enrichment of alloying elements, the martensite / bainite formed in the first step of quenching and cooling has a lower Ac1 temperature than the critical ferrite, and thus becomes the nucleation site of the secondary reverse phase transformation austenite in the second step of critical tempering. At the same time, during the second step of tempering, the alloying elements are highly enriched in the reversed austenite again, further improving the stability of the secondary reversed austenite. In addition, the secondary reversed austenite formed by the second step of tempering is uniformly dispersed, mostly in the form of a film, and small in size. The nano-size effect of austenite stabilizes the residual austenite. Finally, after air cooling, a multiphase structure dominated by critical ferrite + tempered martensite / bainite + fine residual austenite is obtained. The organization type of soft and hard phase matching and the deformation induced plasticity (TRIP) mechanism of residual austenite give the steel plate excellent strength, toughness and crack arrest.

[0011] The outstanding features and remarkable effects of the present invention are mainly reflected in: (1) The present invention uses continuous casting billets to produce high crack arrestability extra-thick steel plates with a maximum thickness of 100 mm. While ensuring product quality, the crack arrest toughness Kca at -10°C is ≥8000N / mm 3 / 2 ; (2) The present invention breaks through the limitation of the compression ratio of the traditional TMCP process for rolling extra-thick plates, refines the grains through the microstructure control technology, improves the core microstructure and performance of the extra-thick steel plate, has a simple process, reduces alloy and production costs, and has a high yield rate; (3) The present invention can be implemented using existing equipment and process conditions in steel mills, without the need for additional investment or equipment modification, and the process is stable, easy to implement, and can be mass-produced; (4) The method of the present invention produces a new type of economical, low-carbon and environmentally friendly steel, which can also be widely used in shipbuilding, bridges, pressure vessels, construction, engineering machinery and other fields to ensure the crack-stopping ability of steel plates. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1 This is the metallographic structure diagram of the steel plate at the 1 / 4 position in the thickness direction of Example 1 of the present invention.

[0013] Figure 2 This is the metallographic structure diagram of the steel plate at the 1 / 2 position in the thickness direction of Example 1 of the present invention. DETAILED DESCRIPTION

[0014] The present invention will be further described below by way of embodiments in conjunction with the accompanying drawings.

[0015] The chemical composition of the steel in the examples is shown in Table 1, with the remainder being Fe and inevitable impurity elements.

[0016] According to the production method described in the present invention, according to the chemical composition of the steel in the above embodiment, a 120t top and bottom double-blown converter is used for smelting, and after refining and vacuum treatment outside the furnace, it is cast into a continuous casting billet with a cross section of 350mm, and then rolled into a steel plate with a thickness of 100mm on a 5000mm double-frame wide and thick plate production line, and then through a heat treatment process of quenching and tempering, a finished steel plate is finally obtained. Afterwards, samples are taken to test the tensile, impact and crack arrest properties of the finished steel plate, and the metallographic structure is observed. The key process parameters of the embodiment steel plate are shown in Table 2, and the actual performance is shown in Table 3.

[0017] It can be seen from the actual performance results in Table 3 that the steel plates of the embodiments of the present invention have good comprehensive mechanical properties and crack arrest performance. Embodiment 1 meets the 32 kg strength level requirement. It can be seen from the attached figure that the multiphase structure mainly composed of critical ferrite + tempered bainite + fine residual austenite is regulated by the online DQ+LT process; Embodiment 2 meets the 36 kg strength level requirement; Embodiment 3 meets the 40 kg strength level requirement; The steel plate produced by the method of the present invention, when the thickness reaches 100 mm, the core -60 ° C impact toughness can still reach more than 200 J, and the elongation reaches more than 30%, and has excellent toughness and plasticity; The crack arrest toughness of the embodiment steel plate is tested by a gradient temperature type double tensile test, and the -10 ° C crack arrest toughness Kca value reaches 8000 N / mm 3 / 2 As mentioned above, the steel plate has high crack arrest performance and can well meet the use requirements of key parts of ultra-large container ships.

[0018] In addition to the above embodiments, various modifications may be made to the embodiments without departing from the scope of the present invention. Any technical solution formed by equivalent replacement or equivalent transformation falls within the protection scope required by the present invention. The scope of the present invention is defined by the claims and their equivalents.

[0019] Table 1 Chemical composition of high crack arrestability extra thick high strength ship plate in the embodiment .

[0020] Table 2 Key process parameters of the steel plate in the embodiment of the present invention .

[0021] Table 3 Physical properties of steel plates in the embodiments of the present invention .

Claims

1. A method for producing a high-crack-arresting, extra-thick, high-strength ship plate, the production process steps comprising: Smelting, continuous casting, heating, rolling, cooling, quenching and tempering, characterized in that: the chemical composition and weight percentage of the steel are: C=0.05%~0.08%, Si≤0.50%, Mn=1.20%~1.60%, P≤0.010%, S≤0.002%, Al=0.015%~0.05%, Nb=0.01%~0.04%, V=0.02%~0.05%, Ti=0.008%~0.02%, Ni=0.20%~0.50%, Cr≤0.20%, Cu≤0.20%, the balance is Fe and unavoidable impurities; the key process steps include: heating furnace temperature 1180~1220℃; rolling adopts controlled rolling, and the final rolling temperature is 820~850℃; cooling adopts rapid water cooling to room temperature, and the cooling rate is ≥5℃ / s; quenching adopts two-phase zone quenching, and the quenching temperature is A c1 +(10~30)℃, quenching time is 3.0min / mm×plate thickness+(15~25)min; tempering adopts critical tempering, and the tempering temperature is A c1 -(20~60)℃, tempering time is 2.5~3.0min / mm×plate thickness min; among which, A c1 It is the starting temperature of the transformation of ferrite to austenite during the heating process.

2. The method for producing a high-crack-arresting, extra-thick, high-strength ship plate according to claim 1, characterized in that: A method for producing a high-crack-arresting, extra-thick, high-strength ship plate with a yield strength of 32 kg, wherein the chemical composition of the steel and its weight percentage are C=0.05%~0.07%, Si=0.15%~0.35%, Mn=1.30%~1.40%, P≤0.010%, S≤0.002%, Al=0.015%~0.050%, Nb=0.01%~0.02%, V=0.02%~0.03%, Ti=0.008%~0.02%, Ni=0.20%~0.30%, and the remainder is Fe and unavoidable impurity elements; the key processes are: the quenching temperature is 720~740℃, and the tempering temperature is 665~695℃.

3. The method for producing a high-crack-arresting, extra-thick, high-strength ship plate according to claim 1, characterized in that: A method for producing a high-crack arresting extra-thick high-strength ship plate with a yield strength of 36 kg, wherein the chemical composition of the steel and its weight percentage are C=0.05%~0.07%, Si=0.15%~0.35%, Mn=1.40%~1.50%, P≤0.010%, S≤0.002%, Al=0.015%~0.050%, Nb=0.02%~0.03%, V=0.03%~0.04%, Ti=0.008%~0.02%, Ni=0.30%~0.40%, Cr=0.10%~0.18%, and the remainder is Fe and unavoidable impurity elements; the key processes are: the quenching temperature is 725~745℃, and the tempering temperature is 660~690℃.

4. The method for producing a high-crack-arresting, extra-thick, high-strength ship plate according to claim 1, characterized in that: A method for producing a high-crack arresting extra-thick high-strength ship plate with a yield strength of 40 kg level, wherein the chemical composition of the steel and its weight percentage are C=0.06%~0.08%, Si=0.15%~0.35%, Mn=1.50%~1.60%, P≤0.010%, S≤0.002%, Al=0.015%~0.050%, Nb=0.03%~0.04%, V=0.04%~0.05%, Ti=0.008%~0.02%, Ni=0.40%~0.50%, Cr=0.10%~0.18%, Cu=0.10%~0.18%, and the remainder is Fe and unavoidable impurity elements; the key processes are: the quenching temperature is 730~750℃, and the tempering temperature is 660~690℃.

Citation Information

Patent Citations

  • High-strength steel plate with superior crack arrestability

    CN101341269A

  • High crack-arresting toughness steel plate with yield strength of 500MPa and production method thereof

    CN102994874A

Cited By

  • Marine crack arrest steel EH47 and preparation method thereof

    CN122406085A